Zyklus und Serie Van Goghs Ansichten des ummauerten Feldes in Saint-Rémy - Baumann, Lukas (Universitätsverlag Göttingen, 2018)
A few weeks before van Gogh admitted himself into a mental hospital in Saint-Rémy in spring 1889 he had written to Gauguin that he wanted to create a "consolatory art for distressed hearts". From his bedroom in the clinic he overlooked an enclosed wheat field. Over the course of a year the seasonal changes inspired Van Gogh to paint a cycle of this wheat field, thereby seeing it as an allegorical representation of the fate of human life, which comforted him.